A panel data analysis on the relationship between corporate governance and bank efficiency - Htay, Sheila Nu Nu; Ab. Rashid, Hafiz Majdi; Adnan, Muhammad Akhyar; Mydin Meera, Ahamed Kameel (2011)

(untitled)
Emerging corporate governance issues in the Asian countries due to the 1997-1998 economic crises makes it much more important to discuss those issues within the context of this region. In developing countries such as Malaysia, a good governance of the banks is crucial for the survival of its economy. Many studies have tried to link the effect of corporate governance on banks’ efficiency (Jain and Thomson, 2008; Chunxia, Shujie and Zongyi, 2009; Lensink, Meesters and Naaborg, 2008). This study investigates the impact of corporate governance on efficiency of Malaysian listed banks by using a panel data analysis.